2011
DOI: 10.1103/physreve.84.056210
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant-induced gradients in the three-dimensional Belousov-Zhabotinsky reaction

Abstract: Scroll waves are prominent patterns formed in three-dimensional excitable media, and they are frequently considered highly relevant for some types of cardiac arrhythmias. Experimentally, scroll wave dynamics is often studied by optical tomography in the Belousov-Zhabotinsky reaction, which produces CO(2) as an undesired product. Addition of small concentrations of a surfactant to the reaction medium is a popular method to suppress or retard CO(2) bubble formation. We show that in closed reactors even these low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 51 publications
(82 reference statements)
1
35
0
Order By: Relevance
“…In addition, a surfactant, 0.05 mM sodium dodecyl sulfate (SDS, Fluka), was added to the reaction medium to reduce the production of CO 2 bubbles [26]. It has been shown that such the low SDS concentration did not cause a significant effect on the excitability of the medium [33].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a surfactant, 0.05 mM sodium dodecyl sulfate (SDS, Fluka), was added to the reaction medium to reduce the production of CO 2 bubbles [26]. It has been shown that such the low SDS concentration did not cause a significant effect on the excitability of the medium [33].…”
Section: Methodsmentioning
confidence: 99%
“…To reduce the production of CO 2 bubbles, the surfactant sodium dodecyl sulfate (SDS) was added at concentrations below its critical micelle concentration [18]. The initial concentrations were 50 mM malonic acid (Merck), 50 mM sodium bromate (Merck), 0.2 mM SDS (Fluka), and 0.5 mM ferroin.…”
Section: A Chemical Preparationmentioning
confidence: 99%
“…Scroll waves were initiated by the partition method [6,7,18,22]. The reaction volume was divided into two compartments with a PET sheet and a cylindrical wave was initiated by immersion of a silver wire (diameter 0.5 mm).…”
Section: B Initiation Of Scroll Wavesmentioning
confidence: 99%
See 2 more Smart Citations